Artificial Insemination in the Perspective of Indonesian Islamic Community Organizations - Ahmad Hidhir Adib; Vina Wardatus Sakinah; M. Ulyaul Umam; Ibnur Rijal Athi'ullah (Santri: Journal of Pesantren and Fiqh Sosial, 2023)
Artificial insemination (IVF) allows couples to have offspring without going through intercourse. This method was only practiced in Indonesia in 1987. In Indonesia itself, Islamic products and laws were heavily influenced by Islamic organizations that had developed massively within them. This study aims to discuss the law regarding the phenomenon of artificial insemination in the view of Islamic organizations in Indonesia. The opinion of the Islamic community organizations used as data sources are Nahdlatul Ulama, Muhammadiyah, and the Indonesian Council of Ulama (MUI). The method used is a literature study with a comparative approach. The study results showed that all mass organizations agreed regarding the conditions for the permissibility of artificial insemination to be carried out by a legal husband and wife. The NU and MUI emphasize more on the aspect of haraam law more because they uphold the spirit of prudence. At the same time, Muhammadiyah focuses more on the legal aspect because it upholds the spirit of hifdzun nasl (safeguarding offspring). There are several differences, namely in the aspect of the sperm retrieval mechanism, who is the recipient and his lineage status.